Implementasi Manajemen Pendidikan Holistik dan Kompetensi Guru dalam Meningkatkan Perkembangan Kognitif Anak Usia Dini (Studi di Kober I’anatul Mubtadin Cijeungjing Ciamis dan Kober Nuurul Qur’an Tasikmalaya) - Daniansah, Daniansah; Kosasih, Kosasih; Mulyanti, Dety (BUDGETING : Journal of Business, Management and Accounting, 2024)
Holistic educational management is indicated by the growth and development of all aspects of development. Inadequate simulation of early childhood growth and development by inappropriate management systems and teacher competency factors has an impact on unpreparedness for entering further education and imperfect utilization of all children's competencies, especially children's cognitive development. The aim of this research is to describe and analyze in more depth the cognitive development of children who both by considering management facts and teacher competency which have been carried out in Kober I'anatul Mubtadiin Ciamis and Kober Nuurul Qur'an Tasikmalaya. The quantitative research method used is a case study design. Data were collected using observation techniques, interviews and filling in questionnaires and documentation. Data analysis was carried out through data reduction, data presentation and drawing conclusions. The research results show that the implementation of holistic education management and teacher competency has a significant influence on early childhood development, especially on children's cognitive development. It is proven by the research results that 49.8% of cognitive development is influenced by holistic education management and teacher competence where the researcher conducted the research. Keywords: Cognitive Development, Holistic Education Management, Teacher Competency.